Key factors of using Crowd-technologies in the activities of Ukrainian local self-government bodies - Larysa, Sokolik (Pressing Problems of Public Administration, 2023)
The purpose of the article is to provide a conceptual justification of the fac-tors, conditions, and limitations regarding the implementation of crowd technolo-gies in the activities of local self-government bodies.It has been established that crowd technologies in local self-government are social technologies that involve the engagement of «informal public» in the govern-ance process through a public offer made by local self-government bodies. These technologies utilize the intellectual potential of online communities to address so-cially significant issues without entering into an employment contract.It is defined that crowd technologies in local self-government are also specif-ic public-private management technologies that introduce civil relations into bu-reaucratic practices. In this regard, it is important to distinguish various types of these technologies, including crowd-sourcing, crowd-funding, crowd-recruiting, crowd-creation, and so on. The utilization of these and other types of crowd tech-nologies in local self-government allows for addressing important tasks for territo-rial communities, such as involving the population in decision-making processes, mobilizing citizen funds for voluntary development of crowd projects through in-formation technologies, searching for talented professionals within the community, and facilitating the creation of new crowd projects by the «informal public».It has been proven that the implementation of crowd technologies as mani-festations of public-private management requires a set of necessary conditions for their integration into the practices of local self-government. These conditions in-clude:Regulatory and legal support for crowd technological activities.Generalization of experience (positive or negative) with crowd tech-nologies.Accurate identification of crowd technology objects.Institutionalization of a public actor interested in crowd technologies.Formation of civic competencies among the population as individual qualities socialized under the influence of civil society.Ensuring informational accessibility of decision-making practices by local self-government bodies and administrative services provided by them, as well as by communal institutions and enterprises.Demonstration of loyalty by local authorities towards organizing work according to the crowd technology model and the willingness of their leaders and officials to collaborate with the public.Development of integrated software products for local self-government bodies based on the principles of open-source software.It is argued that the structure of crowd potential in a territorial community is formed by two main components: the capacity and readiness of the population and local self-government bodies to participate in crowd technologies. Capacity in-cludes awareness of the organization of governance and knowledge of crowd tech-nologies, which is reflected in the societal and governmental understanding of the possibilities for implementing crowd projects at the community level. Readiness consists of the interest in voluntary participation in addressing social issues, the societal values of the population and local self-government bodies, and their moti-vational reasons for participating in crowd projects.